The blood–brain barrier, TWEAK, and neuropsychiatric involvement in human systemic lupus erythematosus and primary Sjögren's syndrome. (November 2018) - Lauvsnes, M B; Tjensvoll, A B; Maroni, S S; Kvivik, I; Grimstad, T; Greve, O J; Harboe, E; Gøransson, L G; Putterman, C; Omdal, R
Objective: A prevailing hypothesis for neuropsychiatric involvement in systemic lupus erythematosus (SLE) and primary Sjögren's syndrome is that brain reactive autoantibodies enter the brain through a disrupted blood–brain barrier. Our aim was to investigate whether TNF-like weak inducer of apoptosis (TWEAK) plays a role in cerebral involvement in human SLE and primary Sjögren's syndrome, and whether an impaired blood–brain barrier is a prerequisite for neuropsychiatric manifestations. Methods: TWEAK was measured in the cerebrospinal fluid and serum and compared with markers of blood–brain barrier permeability (Q-albumin and MRI contrast-enhanced lesions) and S100B, an astrocyte activation marker in 50 SLE and 52 primary Sjögren's syndrome patients. Furthermore, we estimated the general intrathecal B-cell activation (IgG index), measured anti-NR2 antibodies in cerebrospinal fluid, and explored whether these variables were associated with neuropsychiatric manifestations. Results: No associations were found between TWEAK in the cerebrospinal fluid or serum and neuropsychiatric manifestations in SLE nor in primary Sjögren's syndrome patients. Furthermore, no associations were found between neuropsychiatric manifestations and indicators of blood–brain barrier integrity or astroglial activity. Anti-NR2 antibodies were associated with impaired visuospatial processing (odds ratio 4.9, P  = 0.03) and motor functioning (odds ratio 6.0, P  = 0.006). Conclusion: No clinical neuropsychiatric manifestations could be attributed to impaired integrity of the blood–brain barrier, or to TWEAK levels in cerebrospinal fluid or serum in either patient group. The TWEAK concentration was considerably higher in the cerebrospinal fluid than in blood, which indicates intrathecal production. We hypothesize that increased TWEAK and S100B result from immunological stress caused by brain-reactive antibodies produced by brain residing immune cells.